Plant nutrition for sustainable food production and environment : - Loneragan, Jack F. (Kluwer Academic Publishers, 1997)
The XIII International Plant Nutrition Colloquium is the latest in a series which commenced in 1954. It is the first in Asia and possibly the last in the 20th century. This volume of the Proceedings begins with two keynote papers which review achievements in the field of plant nutrition and crop production in this century and discuss future developments in the science and in our society. Recent advances in plant nutrition are reviewed by three other invited papers from the aspects of innovative research technology, molecular biology and rice physiology. Nearly 300 shorter papers report and discuss important findings in plant nutrition: mineral function, ion transport, molecular biology, deficiency and toxicity tolerance, diagnostic techniques, root function, N fixation, microorganisms, rhizosphere, fertilizer, environmental pollution, organic wastes, rice physiology, N and S metabolism, dry matter production and crop quality. Readers will gain an appreciation of current knowledge in all the aspects of plant nutrition relating to sustainable food production and the environment.